G215(P) Development of an Emergency Paediatric Care Programme (EPCP) that builds on the experience learnt from the Royal College of Paediatrics and Child Health's (RCPCH) and Kenyan Paediatric Association's (KPA) Emergency Triage Assessment and Treatment (ETAT+) programme in East Africa. (27th April 2016) - Halbert, J; Soe, K; Myint, AA; Maconochie, I; Wachira, J; Bowyer, J
Abstract : Aims: We describe the development of an EPCP in Myanmar that supports the Ministry of Health priorities. Methods: A partnership between 3 paediatric associations – RCPCH, KPA and Myanmar Paediatric Society (MPS) reviewed ways to reduce child mortality in Myanmar. Kenyan ETAT+ teaching materials were adapted in accordance with Myanmar's Facility-based Integrated Management of Newborn and Childhood Illness manual and national guidelines. Experienced KPA and RCPCH instructors support the development of a faculty of Myanmar EPCP instructors. The development of ETAT+ Teams and implementation plans for each hospital is crucial in minimising barriers to change. Results: A key difference between the EPCP and Kenyan ETAT+ course was the inclusion of dengue, snakebite and beriberi. In 2015, 56 doctors and 47 nurses successfully attended 4 EPCP courses in Myanmar; 2 Voluntary Service Overseas international nurses joined to ensure consistent teaching. The majority had limited experience of simulation and skills training and found these sessions training doctors and nurses together particularly useful. Feedback has been very positive – "excellent training, essential for doctors and nurses" – with 1 participant reporting that they subsequently saved the lives of several children using an intraosseous needle. 14 exceptional participants were invited to attend a Generic Instructor Course which enabled them to "grow in confidence" and develop their teaching styles to "facilitate other people to learn." They were mentored as instructor candidates on 3 subsequent EPCP courses. EPCP participants review the hospital facilities, making recommendations that guide local implementation plans; examples include regular simulation training and patient admission forms. 5 Global Links Volunteers (UK paediatricians) have been recruited to support the local ETAT+ Teams with clinical duties, training, quality improvement, monitoring and evaluation. Conclusions: EPCP is designed to lead to sustainable changes in clinical practice by incorporating South-South training with highly interactive practical teaching; facility improvements to allow learning to be put into practice; leadership and teamwork to create a culture of willingness to change. The formation of a highly-skilled faculty of local instructors maintains the quality of training and reduces the need for international instructors. Support from UNICEF to expand the programme to other regions is further evidence of EPCP success.